2013
DOI: 10.1136/bjophthalmol-2013-303121
|View full text |Cite
|
Sign up to set email alerts
|

Two-year outcomes of intravitreal bevacizumab therapy for macular oedema secondary to branch retinal vein occlusion

Abstract: AimTo determine the 2-year outcomes of intravitreal bevacizumab (IVB) injections in eyes with macular oedema (ME) following branch retinal vein occlusion (BRVO).MethodsOf 105 consecutive eyes (105 treatment-naïve patients) with ME following BRVO, 89 eyes were followed for 2 years after the first injection. During the 2-year follow-up period, patients were examined at least every 3 months and received an IVB injection (1.25 mg/0.05 mL) if they met prespecified retreatment criteria. Rescue grid laser was permitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 22 publications
(26 reference statements)
3
34
0
7
Order By: Relevance
“…A recent study showed that after IVB treatment, there is an increase of retinal venous outflow that may possibly influence the resolution of macular edema [100]. Compared with intravitreal triamcinolone acetonide, intravitreal bevacizumab can achieve better long-term VA outcomes with much lower rate of adverse events (e.g., cataract and glaucoma), despite the fact that triamcinolone acetonide may achieve equal visual acuity and morphology improvement for the first few months right after treatment [101, 102]. Also, IVB can result in better outcome in the recurrent CME, while subthreshold grid laser was completely ineffective [103].…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study showed that after IVB treatment, there is an increase of retinal venous outflow that may possibly influence the resolution of macular edema [100]. Compared with intravitreal triamcinolone acetonide, intravitreal bevacizumab can achieve better long-term VA outcomes with much lower rate of adverse events (e.g., cataract and glaucoma), despite the fact that triamcinolone acetonide may achieve equal visual acuity and morphology improvement for the first few months right after treatment [101, 102]. Also, IVB can result in better outcome in the recurrent CME, while subthreshold grid laser was completely ineffective [103].…”
Section: Treatmentmentioning
confidence: 99%
“…Small studies have demonstrated good clinical outcomes with micropulse laser, for initial visual acuity better or worse than 20/40, although larger studies are necessary [165168]. However, in specific subsets of patients such as recurrent CME after conventional laser treatment, anti-VEGF treatment is still the preferred treatment rather than SMDLP [102]. …”
Section: Treatmentmentioning
confidence: 99%
“…In several clinical studies bevacizumab, one of anti-VEGF agent, was reported to significantly reduce ME and improve visual function in BRVO. [10][11][12] However, its half-life in vitreous is as short as 4.32 days and its effective concentration is maintained for 30 days, thus multiple injection is usually required for maintaining its effect. 13 Multiple injections of bevacizumab increase the risk of injection-related complications such as vitreous hemorrhage, retinal detachment, and endophthalmitis, and it can be an economic burden to patients.…”
Section: Introductionmentioning
confidence: 99%
“…Sixty-nine percent of eyes gained 3 lines, whereas only 7% lost 3 lines. Mean foveal thickness improved from 572 to 220 mm, the average number of injections was 3.8 and 8% of eyes required only one injection [87].…”
Section: Bevacizumabmentioning
confidence: 98%